One Day That Shook the Communist World : The 1956 Hungarian Uprising and Its Legacy - Lendvai, Paul, 1929- (Book collections on Project MUSE., 2008)
On October 23, 1956, a popular uprising against Soviet rule swept through Hungary like a force of nature, only to be mercilessly crushed by Soviet tanks twelve days later. Only now, fifty years after those harrowing events, can the full story be told. This book is a powerful eyewitness account and a gripping history of the uprising in Hungary that heralded the future liberation of Eastern Europe. Paul Lendvai was a young journalist covering politics in Hungary when the uprising broke out. He knew the government officials and revolutionaries involved. He was on the front lines of the student pr.